The Antioxidant and Pro-oxidant Impacts of Varying Levels of Alpha-Lipoic Acid on Biomarkers of Myoglobin Oxidation in Vitro - Farah, Amani Ibrahim; Ahmad, Mousa Numan; Al-Qirim, Tareq Musbah (Jordan Journal of Agricultural Sciences, 2020)
R-alpha-lipoic acid (R-ALA) has been known to protect protein oxidation and lessen the pathogenesis of oxidative-related multiple diseases; however, its dosing remains unresolved. This study aimed to examine whether in vitro R-ALA varying levels would have antioxidant or pro-oxidant impacts on biomarkers of myoglobin oxidation in terms of carbonyls and free thiols for myoglobin upon long-term incubation. Myoglobin (1mg/mL) was concentrated with 6 different concentrations of R-ALA: 50 µM, 100 µM, 500 µM, 1mM, 2mM and 4mM for 30 days at pH 6.6 and temperature 37 °C. Myoglobin oxidative modifications as protein carbonyls and its oxidative defense as free thiols were determined by standard procedures. Thirty-day coincubation of native myoglobin with R-ALA at 500 µM, 1mM, 2mM, and 4mM significantly (p<0.05) elevated carbonyls (2.51±0.19; 2.59±0.22; 2.71±0.32 and 2.79±0.39 nmol/ mg protein respectively) compared to their levels in native control myoglobin (1.67±0.43 nmol/ mg protein) and significantly (p<0.05) decreased free thiols (4.60±0.36; 4.49±0.46; 4.38±0.28 and 4.07±0.39 nmol/ mg protein respectively) against their levels in native control myoglobin (5.71±0.62 nmol/ mg protein). Conversely, coincubation of myoglobin with 50µM and 100µM R-ALA reduced carbonyls (1.02±0.29 and 0.9±0.19 nmol/ mg protein respectively) compared to the control levels (1.67±0.43 nmol/ mg protein) and elevated free thiols (6.1±0.28 and 6.83±0.28 nmol/ mg protein respectively) against control levels (5.71±0.62 nmol/ mg protein) levels; 100µM elicited significant (p<0.05) differences, but 50µM did not. Findings indicate that high levels of R-ALA (0.5-4mM) provoked myoglobin oxidative damage while moderate levels (50-100µM) protected protein upon any spontaneous oxidative damage during long-term coincubation. Thus, R-ALA concentrations, which set the balance between R-ALA pro- and antioxidants, dictate the primary impacts of R-ALA on myoglobin redox status. Additional in vivo investigations are needed to assess the therapeutic insights of current findings.